2021
DOI: 10.1002/anie.202011260
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective N‐Formylation of Amines with CO2 and H2 Catalyzed by Porous Organometallic Polymers

Abstract: The valorization of carbon dioxide (CO2) to fine chemicals is one of the most promising approaches for CO2 capture and utilization. Herein we demonstrated a series of porous organometallic polymers could be employed as highly efficient and recyclable catalysts for this purpose. Synergetic effects of specific surface area, iridium content, and CO2 adsorption capability are crucial to achieve excellent selectivity and yields towards N‐formylation of diverse amines with CO2 and H2 under mild reaction conditions e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…There is considerable interest in the synthesis of N-formyls directly from feedstock chemicals with high atom and economic efficiency. Methods have been developed where methanol, [15][16][17] CO 18 and CO 2 [19][20][21][22][23][24][25][26][27][28] have been exploited as a formyl surrogate employing various catalysts including transition metals. Carbon dioxide (CO 2 ) is a notorious greenhouse gas but an inexpensive, non-toxic, and abundant source of carbon in synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable interest in the synthesis of N-formyls directly from feedstock chemicals with high atom and economic efficiency. Methods have been developed where methanol, [15][16][17] CO 18 and CO 2 [19][20][21][22][23][24][25][26][27][28] have been exploited as a formyl surrogate employing various catalysts including transition metals. Carbon dioxide (CO 2 ) is a notorious greenhouse gas but an inexpensive, non-toxic, and abundant source of carbon in synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Recently, CO 2 has been used as a formyl surrogate for the synthesis of N-formyls in the presence of a reductant. [19][20][21][22][23][24][25][26][27][28] However, most of these reported methodologies require expensive or complex metal based catalysts [20][21][22]24,[26][27][28] as well as ligands along with hydrogen gas or hydrosilanes 19,25 as a source of hydride under high temperature and pressure. Although these reported methods use substoichiometric amounts of catalysts, still these transformations are far from ideal due to limited product scope as well as poor energy and economic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…40 In 2020, Ding and coworkers 41 reported that a Ru-PPh 3 -SO 3 Na@POPs base catalyst exhibited good performance and stability for the synthesis of formamides. Soon after, Tu et al 42 reported that a porous metal−organic polymer (POMP-NHC-Ir) synthesized N,N-dimethylformamide by dimethylamine with CO 2 and H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although CO 2 is safe to utilize, the inherent kinetic inertness and thermodynamic stability limit its application in large-scale formamide synthesis. Currently, many tactics have been developed to obtain formamides by activating CO 2 molecules with hydrosilane, , borohydride, or hydrogen as reducing agents. Notably, H 2 is a more desirable reducing agent due to its higher atomic economy and non-polluting properties than hydrosilane or borohydride.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation